Considerations on the UK Re-Arrest Hazard Data Analysis (How Model Selection Can Alter Conclusions for Policy Development) - WILSON, SIMON; HOULDING, BRETT (My University, 2011)
The offence risk posed by individuals who are arrested, but where subsequently no charge or caution is administered, has been used as an argument for justifying the retention of such individuals? DNA and identification profiles. Here we consider the UK Home Office arrest-to-arrest data analysis, and find it to have limited use in indicating risk of future offence. In doing so, we consider the appropriateness of the statistical methodology employed and the implicit assumptions necessary for making such inference concerning the re-arrest risk of a further individual. Additionally, we offer an alternative model that would provide an equally accurate fit to the data, but which would appear to have sounder theoretical justification. Finally, we consider the implications of using such statistical inference in formulating national policy, and highlight a number of sociological factors that could be taken into account so as to enhance the validity of any future analysis.
58th Congress of the International Statistical Institute
PUBLISHED
Online publication
Dublin, Ireland
Keywords: UK Re-Arrest rates; Smart & Sustainable Planet